Taxonomic studies on Cercospora complex of some leguminous crops - A.K. SARBHOY; MAHENDRA PAL, ANIL KUMAR ARYA, D.K. AGARWAL (Indian Phytopathology, 2002)
The Cercospora complex infecting Vigna radiata (mung bean), Vigna mungo (urd bean), Vigna unguiculata (cowpeas) and Cajanus cajan (pigeon peas) was investigated from diseased leaves collected from Pantnagar, Almora (Uttar Pradesh), Hisar (Haryana) and Delhi, India. C. canescens, Pseudocercospora cruenta, P. dolichi, Mycovellosiella cajani and M. cajani var. indica are described and illustrated.